miR-199a-3p Modulates MTOR and PAK4 Pathways and Inhibits Tumor Growth in a Hepatocellular Carcinoma Transgenic Mouse Model - Elisa Callegari; Lucilla D'Abundo; Paola Guerriero; Carolina Simioni; Bahaeldin K. Elamin; Marta Russo; Alice Cani; Cristian Bassi; Barbara Zagatti; Luciano Giacomelli; Stella Blandamura; Farzaneh Moshiri; et al. (Elsevier, 2018)
Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related death worldwide. Prognosis is poor, and therapeutic options are limited. MicroRNAs (miRNAs) have emerged as potential therapeutic molecules against cancer. Here, we investigated the therapeutic efficacy of miR-199a-3p, an miRNA highly expressed in normal liver and downregulated in virtually all HCCs. The therapeutic value of miR-199a-3p mimic molecules was assayed in the TG221 mouse, a transgenic model highly predisposed to the development of liver cancer. Administration of miR-199a-3p mimics in the TG221 transgenic mouse showing liver cancer led to a significant reduction of number and size of tumor nodules compared to control animals. In vivo delivery confirmed protein downregulation of the miR-199a-3p direct targets, mechanistic target of rapamycin (MTOR) and p21 activated kinase 4 (PAK4), ultimately leading to the repression of FOXM1. Remarkably, the anti-tumor activity of miR-199a-3p mimics was comparable to that obtained with sorafenib. These results suggested that miR-199a-3p may be considered a promising HCC therapeutic option.